Applications of Remote Sensing and GIS in Monitoring Surface Water of Al-Razzaza Lake: A Review - Afrah Medhat Rashed; Mufid Alhadithi; Fareed M. Alattar; Fayez Ahamd Massarwa (Journal of Techniques)
Al-Razzaza Lake, which was established in 1969 to protect the southern regions from heavy rains, is a part of the western plateau and is characterized by a semi-arid climate, hot in summer and cold in winter. The lake water level decreased in the past ten years due to the lack of rain and high temperatures, which affected the water quality and quantity, so it was studied and monitored the decline of the water level and calculate the surface area of the lake by several researchers using remote sensing techniques integrated with the GIS environment. Several researches were reviewed in this study, which dealt with the use of satellite images taken at different periods with the help of Geographic Information Systems (GIS) to detect change in the areas covered by Al-Razzaza Lake. Studies have shown that the area of the lake gradually decreased from 1990 to 2018 at a rate of about 1285 km2, then recovered slightly since 2018 at a rate of 118 km2. The results of the studies also showed that there is a real threat to the environment of Al-Razzaza Lake as a result of the significant deterioration that affects the water quality and the environment in the region. Consequently, researchers are required to expand the study of this problem to provide recommendations and propose appropriate solutions to reduce the resulting risks.